Suppression of stacking-fault expansion in 4H-SiC PiN diodes using proton implantation to solve bipolar degradation - Masashi Kato; Ohga Watanabe; Toshiki Mii; Hitoshi Sakane; Shunta Harada (Scientific Reports, 2022)
Abstract 4H-SiC has been commercialized as a material for power semiconductor devices. However, the long-term reliability of 4H-SiC devices is a barrier to their widespread application, and the most important reliability issue in 4H-SiC devices is bipolar degradation. This degradation is caused by the expansion of single Shockley stacking-faults (1SSFs) from basal plane dislocations in the 4H-SiC crystal. Here, we present a method for suppressing the 1SSF expansion by proton implantation on a 4H-SiC epitaxial wafer. PiN diodes fabricated on a proton-implanted wafer show current–voltage characteristics similar to those of PiN diodes without proton implantation. In contrast, the expansion of 1SSFs is effectively suppressed in PiN diodes with proton implantation. Therefore, proton implantation into 4H-SiC epitaxial wafers is an effective method for suppressing bipolar degradation in 4H-SiC power-semiconductor devices while maintaining device performance. This result contributes to the development of highly reliable 4H-SiC devices.